Memellander/Klaipėdiškiai Identity and German-Lithuanian Relations in Lithuania Minor in the Nineteenth and Twentieth Centuries - Vareikis, Vygantas (Sociologija. Mintis ir veiksmas, 2001)
The aim of this article is to discuss the of a double identity in the Klaipėda region in the first half of the twentieth century. The author develops the discussion around a few questions: how the Lithuanians who lived in Prussia adopted German values and social conventions by simultaneously maintaining their own language and identity; what political factors were influential in the development of identity of Prussia’s Lithuanians; how did the double identity of Lithuania Minor influence the Lithuanian self-understanding.